Targeting irradiation-induced mitogen-activated protein kinase activation in vitro and in an ex vivo model for human head and neck cancer - Affolter, Annette; Muller, Marie France; Sommer, Katharina Sophia; Stenzinger, Albrecht; Plath, Karim; Lorenz, Katja; Wolf, Thomas; Sharma, Sarika; Wolf, Janina Luisa; Weber, Klaus-Josef; Freier, Kolja; Plinkert, Peter K.; et al. (Head & neck, 2016)
Background Despite new radiotherapeutic strategies, radioresistance in head and neck squamous cell carcinoma (HNSCC) remains a major problem. Preclinical model systems are needed to identify resistance mechanisms in this heterogeneous entity. Methods We elucidated the interplay among mitogen-activated protein kinase (MAPK)-inhibition, radiation, and p53 mutations in vitro and in a novel ex vivo model derived from vital human HNSCC samples. HNSCC cell lines (p53WT/mut) were treated with the mitogen-activated protein kinase (MEK)-inhibitor PD-0325901 and subsequently irradiated. Radiosensitization was functionally assessed and evaluated in the ex vivo model. Results We observed a pronounced irradiation-induced extracellular signal-regulated kinase (ERK) phosphorylation in 2 cell lines, which was independent of their p53 mutation status and associated with PD-0325901-related radiosensitization in a clonogenic assay. Heterogeneity in irradiation-induced ERK phosphorylation and in radiosensitization after MEK-inhibition was also reflected in the ex vivo model. Conclusion We provide experimental evidence for radiosensitizing effects of PD-0325901 in HNSCC. The ex vivo culture technology might offer a promising tool for individualized drug efficacy testing. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2049-E2061, 2016